Answer:
7
Explanation:
Quadratic Equation: 3x² - 24x + 72
The form we are to convert the equation to:
3x² - 24x + 72
a(x + b)² + 72
3(x² - 8x + 24)
Step 1
Make the Quadratic equation (x² - 8x) in the bracket factorisable using completing the square method
3( x² - 8x +(- 8/2)²) + 24
3( x² - 8x + 16 = -24 + 16
3( x² - 8x + 16 + 8 = 0)
3( x² - 8x + 16) + 8
3( x² - 4x + 4x + 16) + 8
3( x(x - 4) -4(x - 4) + 8
3((x - 4)(x - 4) )+ 8
3( (x - 4)² + 8
Using this form
a(x + b)² + c
a = 3
b = -4
c = 8
We were asked to add up constants a, b, c
Therefore,
3 +(-4) + 8
= 7